2021
DOI: 10.1038/s12276-020-00547-x
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid dynamics in ex vivo lung cancer and normal lung explants

Abstract: In cancer cells, metabolic pathways are reprogrammed to promote cell proliferation and growth. While the rewiring of central biosynthetic pathways is being extensively studied, the dynamics of phospholipids in cancer cells are still poorly understood. In our study, we sought to evaluate de novo biosynthesis of glycerophospholipids (GPLs) in ex vivo lung cancer explants and corresponding normal lung tissue from six patients by utilizing a stable isotopic labeling approach. Incorporation of fully 13C-labeled glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 45 publications
(62 reference statements)
0
15
0
Order By: Relevance
“…Two plasma lipids, cholesterol esters (C18:2) and SM (22:0), were shown to discern patients with SqCC patients from high‐risk individuals and, hence, could be useful in SqCC screening and early detection 116 . PE levels have been found to be significantly elevated in lung cancer tissues compared with normal lung tissues and, thus, can serve as a potential biomarker in lung cancer 117 …”
Section: Exploiting Cancer‐associated Lipid Pool Alterations and Memb...mentioning
confidence: 99%
“…Two plasma lipids, cholesterol esters (C18:2) and SM (22:0), were shown to discern patients with SqCC patients from high‐risk individuals and, hence, could be useful in SqCC screening and early detection 116 . PE levels have been found to be significantly elevated in lung cancer tissues compared with normal lung tissues and, thus, can serve as a potential biomarker in lung cancer 117 …”
Section: Exploiting Cancer‐associated Lipid Pool Alterations and Memb...mentioning
confidence: 99%
“…Under normal circumstances, ETNK2 is highly expressed in the liver and reproductive tissues [13]. Some studies have confirmed that increased expression of ETNK2 is closely related to liver metastasis in gastric cancer [16], lung adenocarcinoma [18], and lung squamous cell carcinoma [18]. At present, there is no literature concerning the relationship between ETNK2 and thyroid malignant tumours, so we investigated this relationship to explore new molecular markers of PTC.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that methylation of the ETNK2 gene promoter helps laryngeal cancer cells resist radiation [17]. ETNK2 expression is significantly upregulated in lung adenocarcinoma and squamous cell carcinoma [18]. After silencing ETNK2 in MDA-MB-231 cells, cell viability was significantly reduced [19].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanistic clarification of this issue requires carrying out a specific study. However, it is known that cancer cells rewire their metabolism to produce more PE than healthy cells, and this is associated with enhanced expression of the genes for PE biosynthesis ( 74 ).…”
Section: Discussionmentioning
confidence: 99%